Pengaruh Media Teka Teki Silang terhadap Hasil Belajar Siswa pada Materi Operasi Hitungan Campuran dalam Pembelajaran Matematika Kelas IV - Burhanudin Elfany Alamsyah; Sunanto Sunanto; Afib Rulyansah; Sri Hartatik (Departement of Mathematics Education, 2023)
The purpose of this research is to ascertain how Mathematical Crossword Puzzle Media affects fourth-grade students at SDN Semolowaru 1 Surabaya's learning outcomes. This review utilizes a quantitative methodology with the One Gathering Pretest-Posttest technique. The subjects of this review were 4th grade understudies at SDN Semolowaru 1 Surabaya. The study was carried out on February 28, 2023. Pre- and post-tests were used as data collection techniques. This study's validation employs SPSS 26.0 calculations and an expert validator. The descriptive quantitative analysis method with two-tailed paired t-test analysis was used to analyze the data. The consequences of this study demonstrate that there are contrasts in understudy learning results when the utilization of Crossword Puzzle Media with an expansion in the normal worth of 73.39. It is evident from the output test statistics of the paired t-test (2-tailed), which are shown to be sig (2-tailed) 0.000 0.05, that Ha is accepted. This means that there is a difference between the learning outcomes from the Pretest and Posttest scores, and it is possible to draw the conclusion that the Mathematical Crossword Puzzle Media has an effect on improving the learning outcomes of students in class IV SDN Semolowaru 1 Surabaya.